Interacciones medicamentosas en pacientes hipertensos con atención ambulatoria en un hospital militar del oriente peruano, año 2021 - Gonzales Burga, Ana Rosa (2022)
Arterial hypertension (HTN) is a chronic disease that requires lifelong pharmacological treatment. Objective: To determine the drug interactions presented in hypertensive patients with outpatient care in a military hospital in eastern Peru, year 2021. Methodology: It was an observational, descriptive and retrospective study whose population consisted of 72 patients from the Arterial Hypertension program, who were brought him into the studio. Results: The highest proportion of patients were older adults, male and received more than one medication; 87.5% of hypertensive patients presented more than one drug interaction, mostly of the pharmacokinetic type and, due to its severity, significant or moderate; the most frequent interactions correspond to associations between drugs for cardiovascular use with aspirin (30.8%) and celecoxib (5.1%), diuretics (5.4%), lipid-lowering drugs (4.0%), insulin (6 .5%) and other hypoglycemic (2.8%) ; 66.7% of patients ended up with more than one diagnosis. Conclusion: Drug interactions were mostly significant or moderate and pharmacodynamic. The most frequent being the associations between drugs for cardiovascular use with aspirin and celecoxib; with centrally acting analgesics, diuretics, lipid-lowering agents, insulin and other hypoglycemic agents.